2021
DOI: 10.5114/kitp.2021.107469
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the morphological and clinical features of left anterior descending myocardial bridging with multi-detector computed tomography

Abstract: Aim The aim of the study was to assess the incidence, localization, depth, length of myocardial bridging (MB) with left anterior descending (LAD), systolic compression ratio, atherosclerotic plaque localization and degree of stenosis by 256-slice multi-detector computed tomography (MDCT). Material and methods Computed tomography (CT) scans from a total of 3947 patients who underwent MDCT were reviewed retrospectively for LAD MB. A diastolic and systolic dataset with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…MDCT is currently a rapid and adequate test for the diagnosis of MB, which allows the evaluation of the coronary arteries and their relationship with other anatomical structures. [ 42 ] As a noninvasive test, it is comparable to IVUS in terms of accuracy and can be considered as an alternative to CAG in the diagnosis of MB. [ 43 ] This test performs image reconstruction after scanning, and MB is diagnosed when coronary arteries are covered by myocardium of varying thickness, with narrowing of the lumen during systole and re-dilation of the lumen during diastole.…”
Section: Discussionmentioning
confidence: 99%
“…MDCT is currently a rapid and adequate test for the diagnosis of MB, which allows the evaluation of the coronary arteries and their relationship with other anatomical structures. [ 42 ] As a noninvasive test, it is comparable to IVUS in terms of accuracy and can be considered as an alternative to CAG in the diagnosis of MB. [ 43 ] This test performs image reconstruction after scanning, and MB is diagnosed when coronary arteries are covered by myocardium of varying thickness, with narrowing of the lumen during systole and re-dilation of the lumen during diastole.…”
Section: Discussionmentioning
confidence: 99%
“…The intramyocardial bridge is considered a congenital coronary anomaly, it is described as a segment of a major epicardial coronary artery that passes deeply into the myocardium. 1 It was first recognised by Reyman et al in an autopsy and then described in angiography images by Portman et al 2,3 Although it can be observed in any epicardial artery, it is most commonly reported in the mid-section of the left anterior descending artery (LAD). 4 The revascularisation of the LAD affects both the early and late postoperative outcomes of coronary artery bypass grafting (CABG).…”
Section: Anah Tar Ke LI Me Ler: Koroner Arter Baypas; Miyokardiyal Kö...mentioning
confidence: 99%
“…Eventually, platelet aggregation and lipoprotein deposition contribute to atherosclerosis in the coronary artery proximal to the MB [ 6 ]. Currently, coronary computed tomography angiography (CCTA) is considered to be an excellent tool in the noninvasive evaluation of MB parameters due to its effective visualization of MBs [ 7 ]. However, the value of radiological MB parameters in predicting coronary atherosclerosis risk is controversial.…”
Section: Introductionmentioning
confidence: 99%